The adoption of minimalist lifestyle through Instagram (a study about the influence of motives, attitudes, subjective norms, and perceived behavioral control on behavior through behavioral intention on Instagram followers @lyfewithless) - Ekky Ayu Niasari; Revta Fariszy (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2023)
The Lyfe With Less community on Instagram is an educational platform providing insights into the significance of adopting a minimalist lifestyle tailored to its followers' motives for accessing the media. The minimalist lifestyle is characterized by exercising self-control and prioritizing essential elements. Moreover, behavioral intentions play a crucial role as a direct determinant of behavior; when individuals possess the intention to act, their behavior aligns accordingly. This study investigates how motives and planned behavior, including attitudes, subjective norms, and perceived behavioral control, influence the adoption of a minimalist lifestyle among Instagram followers @lyfewithless, with behavioral intention acting as an intervening variable. The research methodology employed is descriptive quantitative, path analysis, and Sobel test, utilizing a sample of 100 Instagram followers @lyfewithless. The study draws upon the theories of uses and gratification and the theory of planned behavior to guide its analysis. The findings reveal that attitudes, subjective norms, and behavioral intentions directly impact behavior. However, motives and perceived behavioral control do not directly affect behavior. Interestingly, the behavioral intention variable mediates the relationship between motives and perceived behavioral control on behavior. Nonetheless, behavioral intention does not mediate the effect of attitudes and subjective norms on behavior.